STUDI KOMUNITAS FILUM MOLLUSCA DI ZONA INTERTIDAL PANTAI SUKAERLARAN DESA KENEBIBI KECAMATAN KAKULUK MESAK KABUPATEN BELU - Gonsianus Pakaenoni (SAINTEKBU, 2019)
The area which has recently received considerable attention is the coastal region / region. This is because the coastal region / region has a diverse wealth that can be utilized by the surrounding community as a source of the main food ingredients that are rich in animal protein content. Mollusca comes from Latin "mollis" which means soft. In addition to soft body also has a shell that functions as an outer framework (Rusyana, 2011). The benefits of Mollusca for humans include as a source of protein, animal feed ingredients, industrial materials, jewelry, fertilizer materials and medicines (Dibyowati, 2009). This research was conducted in the intertidal zone of Sukaerlaran beach, Kenebibi Village, Kakuluk Mesak District, Belu Regency. The results showed that the density of mollusks ranged from 4.25 Ind / m2 - 13.25 Ind / m2 which were spread in 4 roaming areas. The roam area I has the highest density value of 13.25 Ind / m2. The average value of the relative density of mollusks ranges from 0.11% - 0.34%. Of the four roaming areas, roaming areas that have the highest relative density are range I of 0.34%. The diversity index value in all 4 home ranges is relatively low. The dominance index value indicates that the entire range (4 roaming areas) is in the low category with a range of values ​​between 0.0120 - 0, 1169.